TRAIP enhances progression of tongue squamous cell carcinoma through EMT and Wnt/β-catenin signaling by interacting with DDX39A - Litong Liu; Ping Wang; Cheng Guo; Li Song; Lifang Chen; Hongbing Qi; Yangyang Zheng; Xiaoming Xing; Chengqin Wang (BMC Cancer)
Abstract Background Tongue squamous cell carcinoma (TSCC) is one of the most common malignant tumors with high mortality and poor prognosis. Its incidence rate is increasing gradually. Tumor necrosis factor receptor-associated factor interacting protein (TRAIP), as a factor related to several tumors, reveals that its gene expression is different between normal tissue and primary tumor of head and neck squamous cell carcinoma using bioinformatics analysis. Method In our study, TCGA database, immunohistochemistry, proliferation assay, colony formation, wound healing assay, Transwell, cell cycle analysis and tumor xenografts model were used to determine the expression and functions of TRAIP in TSCC. Result We found that TRAIP may promote the proliferation, migration and invasion of TSCC. Furthermore, the results of bioinformatics analysis, mass spectrometry and co-immunoprecipitation suggested that DDX39A may be a TRAIP interacting protein. DDX39A has been proven to be an oncogene in several tumors, which may have an important effect on cell proliferation and metastasis in multiple tumors. In addition, the high expression of DDX39A implies the poor prognosis of patients. Our study demonstrated that TRAIP probably interact with DDX39A to regulate cell progression through epithelial-mesenchymal transition and Wnt/β-catenin pathway. In addition, we show that the necessary domain of DDX39A for the interaction between DDX39A and TRAIP region. Conclusion These results indicate that TRAIP is important in occurrence and development of TSCC and is expected to become the new promising therapeutic target.